Donor Genotype in the Interleukin-7 Receptor α-Chain Predicts Risk of Graft-versus-Host Disease and Cytomegalovirus Infection after Allogeneic Hematopoietic Stem Cell Transplantation - Kielsen, Katrine; Enevold, Christian; Heilmann, Carsten; Sengeløv, Henrik; Pedersen, Anders Elm; Ryder, Lars P.; Müller, Klaus (Frontiers in Immunology, 2018)
The efficacy of allogeneic hematopoietic stem cell transplantation (HSCT) is challenged by acute and chronic graft-versus-host disease and viral infections due to long-lasting immunodeficiency. Interleukin-7 (IL-7) is a cytokine essential for de novo T-cell generation in thymus and peripheral T cell homeostasis. In this study, we investigated the impact of the single nucleotide polymorphism rs6897932 in the IL-7 receptor α-chain (IL-7Rα) which has previously been associated with several autoimmune diseases. We included 460 patients undergoing allogeneic HSCT after a myeloablative conditioning. Patients had a median age of 26.3 years (0.3-67.0 years), and 372 (80.9%) underwent HSCT for malignant diseases. Donors were matched sibling donors (n=147), matched unrelated donors (n=244) or mismatched unrelated donors (n=69), and the stem cell source were either bone marrow (n=329) or peripheral blood (n=131). DNA from donors was genotyped for the IL-7Rα SNP rs6897932 using an allele-specific primer extension assay (CC: n=252, CT: n=178; TT: n=30). The donor T allele was associated with a higher risk of grade III-IV acute GVHD (HR=2.0, 95% CI=1.1-3.8, P=0.034) and with significantly increased risk of extensive chronic GVHD (HR=2.0, 95% CI=1.1-3.6, P=0.025) after adjustment for potential risk factors. In addition, the TT genotype was associated with a higher risk of CMV infection post-transplant (HR=2.4, 95% CI=1.2-4.3, P=0.0068). Numbers of T cells were significantly higher on day +60 in patients receiving a rs6897932 TT graft (CD3+: 109% increase, P=0.0096; CD4+: 64% increase, P=0.038; CD8+: 133% increase, P=0.011). Donor heterozygosity for the T allele was associated with inferior overall survival (HR=1.7, 95% CI=1.2-2.3, P=0.0027) and increased TRM (HR=2.3, 95% CI=1.3-4.0, P=0.0047), but was not associated with the risk of relapse (P=0.35). In conclusion, the IL-7Rα rs6897932 genotype of the donor is predictive of acute and chronic GVHD, CMV infection and mortality following HSCT. These findings indicate that IL-7Rα SNP typing of donors may optimize donor selection and facilitate individualization of treatment in order to limit treatment-related complications.